Development and validation of an empirical instrument to quantify perceptions of information and communication technology (ICT) use capacity in extension networks - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The instrument was administered to network members (n = 122) associated with the Global Forum for Rural Advisory Services and the results of this research were published in a journal.